The influence of public environmental concern on the rural living environment in China - Zhang, Wenguang; Jing, Qinlei; Lu, Ji (Frontiers in Sustainable Food Systems, 2024)
Background: Despite China's economic growth, rural living environments have often lagged behind. While public participation is gaining importance in environmental governance, the magnitude and mechanism of its impact remain understudied. Purpose: This research investigates the relationship between public environmental concerns and the rural living environment in China and explores how public concerns impact living conditions. Methodology: Using panel data from 245 prefecture-level cities (2012-2021), we employed the entropy method to measure rural living environment scores and used fixed-effect models to analyze the relationship between public concern and the living environment. Results: The findings demonstrate a positive relationship between strong public environmental concerns and improved rural living environments. Further analysis suggests that local government environmental attention acts as a partial mediator in this relationship. Conclusion: This study reveals that public participation can influence government policies, ultimately leading to positive environmental outcomes. Promoting public participation in environmental governance is crucial for improving the rural living environment.